Risk factors of progression of chronic kidney disease patients under conservative treatment - Ghonemy, Tarek A.; Farag, Salama Elsayed; Soliman, Sameh A. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic kidney disease (CKD) is recognized as a major health problem affecting approximately 13% of the US population. Early identification and treatment of risk factors of progression of chronic kidney disease can provide marked benefits later in the term of delaying progression to renal replacement therapy. Methods: The medical chart for 92 CKD patients on regular follow up in low clearance clinic with GFR below 20 ml/min were retrospectively reviewed annually for 4 years regular follow up period. The following variables were recorded for each patient: non-modifiable variables (Age, sex, nationality, BMI, systolic and diastolic blood pressure, smoking status, causes of kidney disease, diabetes status, hepatitis status, medication used (like ACEi/ARBs and Sodium bicarbonate) and modifiable variables which includes: Serum albumin, potassium level, serum bicarbonate level, level of proteinuria, rate of GFR decline (Delta GFR) /year, total cholesterol level and hemoglobin level. Then they were divided into 2 groups according to the endpoint during the follow up period. Group 1 include patients did not start dialysis yet and group 2 which include patients who started dialysis during their regular follow up period. Results: There is no statistically significant differences between the two groups regarding Age , sex, systolic and diastolic blood pressure and Body Mass Index( BMI), serum albumin and haemoglobin levels (p 0.295, 0.317, 0.220, 0.181,0.805, 0.884 and 0.451 respectively). There is no statistically a difference between the two groups regarding serum potassium level and serum total cholesterol level (p 0.515 and 0.517 respectively). Diabetic patients started dialysis earlier than non-diabetics with statistically significant difference between the two groups (p 0.029). The patients who weren’t taking ACEi or ARBs started dialysis earlier than those who were taking (p 0.005), while there was no significant differences between the two groups regarding sodium bicarbonate intake (p 0.256). Low sodium bicarbonate level and severity of proteinuria are of significantly important risk factors for progression of CKD disease (p 0.006 and 0.029 respectively). Conclusions: The most important risk factors for rapid progression are presence of diabetes, severity of proteinuria and low serum bicarbonate level in advanced stages of chronic kidney disease. Early recognition of these risk factors and their correction may retard the progression of CKD, which will delay the need for renal replacement therapy. In addition, ACEI or ARBs intake are almost renoprotective and may delay the rapid progression of chronic kidney disease especially in proteinuric patients.